Emerging patterns of cannabis and other substance use in Aboriginal communities in Arnhem Land, Northern Territory: A study of two communities - Clough, A.; D'Abbs, P.; Cairney, S.; Gray, Dennis; Maruff, P.; Parker, R.; O'Reilly, B. (2004)
Objective: A recent rise in cannabis use in Indigenous communities in northern Australia may have compounded existing patterns of other substance use. This paper describes these patterns in Arnhem Land in the 'Top End' of the Northern Territory (NT). Economic impacts of the cannabis trade are also described. Methods: In a descriptive cross-sectional study, random samples included 336 people (169 males, 167 females) aged 13-36 years. Consensus classification of life-time and current use of cannabis, alcohol, tobacco, kava, inhalants (petrol) and other drugs was derived based on health workers' proxy assessments. A sample (n=180, aged 13-36)was opportunistically recruited for interview. Life-time cannabis users among those interviewed (n=131, 81 males, 50 females) described their current cannabis use, usual quantities purchased and consumed, frequency and duration of cannabis use and other substance use. Results: In the random samples, 69% (63%-75%) of males and 26% (20%-31%) of females were life-time cannabis users (OR=7.4, 4.5-12.1, P<0.001). The proportion of males currently using cannabis was 67% (60%-73%) while the proportion of females currently using it was 22% (16%-27%) (OR=7.9, 4.8-13.1, P<0.001). Current cannabis users were more likely than non-users to be also using alcohol (OR=10.4,4.7-23.3, P<0.001), tobacco (OR=19.0, 7.9-45.8, P<0.001) and to have sniffed petrol 3 (OR=9.1, 4.6-18.0, P<0.001) but were less likely to be using kava (OR=0.4, 0.2-0.9, P<0.001).Among those interviewed, higher tobacco consumption in current users and greater alcohol use in life-time users was associated with increased cannabis use. Conclusions: Action is required to reduce cannabis use especially in combination with other substances.